2019
DOI: 10.7759/cureus.4381
|View full text |Cite
|
Sign up to set email alerts
|

The Use of 3D Printed Vasculature for Simulation-based Medical Education Within Interventional Radiology

Abstract: Three-dimensional (3D) printing has become a useful tool within the field of medicine as a way to produce custom anatomical models for teaching, surgical planning, and patient education. This technology is quickly becoming a key component in simulation-based medical education (SBME) to teach hands-on spatial perception and tactile feedback. Within fields such as interventional radiology (IR), this approach to SBME is also thought to be an ideal instructional method, providing an accurate and economical means t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 11 publications
3
34
0
2
Order By: Relevance
“…In a similar fashion, previously, 3D models have been used for educational purposes to rehearse insertion of guidewires and stents together, giving the sense of human arterial texture. [ 12 ] It was concluded that 3D models were superior to conventional teaching models for anatomical teaching and femoral vessel access training. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a similar fashion, previously, 3D models have been used for educational purposes to rehearse insertion of guidewires and stents together, giving the sense of human arterial texture. [ 12 ] It was concluded that 3D models were superior to conventional teaching models for anatomical teaching and femoral vessel access training. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…The 3D printed AAA model used in this study was a re-print of the AAA pathology model used in a study by Goudie et al [3]. The 3D printed AAA model ( Figure 1) and product evaluation surveys ( Figure 2) were distributed to a few Experts at St. Clare's Mercy Hospital in St. John's, Newfoundland.…”
Section: Methodsmentioning
confidence: 99%
“…The 3D printed AAA model used in this study was a re-print of the AAA pathology model used in a study by Goudie et al [ 3 ]. The model was printed in TPU95A (NinjaFlex Cheetah, Fenner Drives, Inc., Hessle, UK) on an Ultimaker 3 3D printer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations